The Effect of Prevention Aspects, Assessment Aspects, Internal Failure Aspects, and External Failure Aspects on the Benefits of Construction Company Projects - Gunaldi Gunaldi; Tukhas Shilul Imaroh (Syntax Corporation Indonesia, 2022)
Several construction projects of PT. Wijaya Karya (Persero) Tbk. experienced many records of product deviations that required repairs to be accepted by the employer. Quality costs (prevention costs, costs, internal failure costs, and external failures) planned by project management are still low on average 1% - 2%. The decline in profit in the last 3 years, namely from 2019 to 2021, is very likely due to the cost of repairs due to poor quality. This study aims to determine the effect of prevention, appraisal, internal failure, and external failure costs on the profitability of construction company projects. The population of this research is construction company employees who have managerial positions, with a total sample of 50 people. The analytical method used in this research is multiple linear regression analysis using the SPSS computer program. The results of the study found that prevention costs, appraisal costs, internal failure costs, and external failure costs had an effect both individually and simultaneously on the profitability of construction company projects.